Influence of shot peening on high-temperature corrosion and corrosion-fatigue of nickel based superalloy 720Li - Gibson, Grant J.; Perkins, K. M.; Gray, Simon; Leggett, A. J. (Taylor and Francis, 2016)
High-temperature corrosion fatigue, a combination of corrosion with a fatigue cycle, is an emerging generic issue affecting power generation and aero gas turbine engines and has the potential to limit component life. Historically, surface treatments, such as shot peening have been used to improve component life and have been optimised for fatigue response. Research into optimisation of shot peening techniques for hot corrosion and high-temperature corrosion fatigue has shown 6–8A 230H 200% coverage to provide overall optimum performance for nickel-based superalloy 720Li based on the limited data within this study. Utilisation of electron backscatter diffraction techniques, in combination with detailed assessment of corrosion products have been undertaken as part of this work. The resultant cold-work visualisation technique provides a novel method of determining the variation in material properties due to the shot peening process and the interaction with hot corrosion. Through this work it has been shown that all three shot peening outputs must be considered to minimise the effect of corrosion fatigue, the cold work, residual stress and surface roughness. Further opportunity for optimisation has also been identified based on this work.
Keywords: Nickel; Corrosion fatigue; Hot corrosion; Sulphidation